Challenges in Implementing English as a Medium of Instruction in Non-English Basic Level Schools - Bantawa Rai, Lalita; Pandey, Shiv Ram; Tripathi, Yasodham; K. Geetha, (A Bi-annual South Asian Journal of Research & Innovation, 2025)
This study aimed to explore the challenges in implementing English as a medium of instruction at the basic level schools of Ilam district. The research method selected for the study was qualitative in nature. To meet the objectives of the study, 10 English and non-English teachers and 10 students of basic level from two community schools located in Suryodaya Municipality, Ilam were selected as participants. The participants were selected using a purposive sampling strategy. The researcher collected data by using an open-ended interview. The collected data were first transcribed and then analysed based on the thematic data analysis method. After analysis and interpretation of data, it was found that teachers are facing numerous challenges in implementing English as a Medium of Instruction (EMI) in community schools in Suryodaya Municipality, Ilam. The challenges include limited English language proficiency among teachers, insufficient training and resources, diverse classroom dynamics, assessment difficulties, and inadequate support from educational stakeholders. Additionally, the limited use of English outside the classroom, parental involvement issues, and a lack of adequate support from responsible sectors further complicate EMI implementation. Students are also facing challenges, including fear of making mistakes, insufficient English language exposure outside of class, challenges in transitioning from Nepali to English instruction, and difficulties in understanding academic content delivered in English.